2020
DOI: 10.1016/j.apcatb.2019.118387
|View full text |Cite
|
Sign up to set email alerts
|

Embedded Ni nanoparticles in CeZrO2 as stable catalyst for dry reforming of methane

Abstract: Ni nanoparticles embedded in CeO2 (Ni@CeO2) and CeZrO2 (Ni@CeZrO2) were synthesized by sol-gel method and compared with a Ni/CeO2 prepared by support impregnation. The performance of the catalysts was investigated for dry reforming of methane reaction. In situ XRD, XANES and TEM showed that Ni embedded in CeO2 improved the resistance to sintering along the reduction at 800 o C. Doping ceria with zirconia inhibited the growth of Ni particles and increased the oxygen mobility. SEM, TEM, Raman spectroscopy and TG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
57
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 139 publications
(59 citation statements)
references
References 53 publications
2
57
0
Order By: Relevance
“…However, the intensity of this line starts to decrease when the sample is heated at 200 °C and it is no longer observed after reduction at 800 °C. According to the literature [13,31], the reduction of ceria-based materials leads to the shift of the lines characteristic to CeO2 to lower angles due to the conversion of Ce 4+ to Ce 3+ species but the intensities of these lines do not change. Therefore, what is causing the disappearance of the CeO2 lines during reduction?…”
Section: 1-catalyst Characterizationmentioning
confidence: 97%
See 3 more Smart Citations
“…However, the intensity of this line starts to decrease when the sample is heated at 200 °C and it is no longer observed after reduction at 800 °C. According to the literature [13,31], the reduction of ceria-based materials leads to the shift of the lines characteristic to CeO2 to lower angles due to the conversion of Ce 4+ to Ce 3+ species but the intensities of these lines do not change. Therefore, what is causing the disappearance of the CeO2 lines during reduction?…”
Section: 1-catalyst Characterizationmentioning
confidence: 97%
“…Therefore, the limitation of the Ni particle sintering process is crucial to prevent the carbon formation during the DRM at high temperature. The catalyst design enables the control of the metal particle size for instance by embedded the metal particle in the oxide matrix [13] or by generating porosity in which the metal particle can be confined [14].…”
Section: Ch4 + Co2 ↔ 2 Co + 2h2mentioning
confidence: 99%
See 2 more Smart Citations
“…As shown in Figure 16, the NAC-SG catalyst displayed much higher feed conversion, product yield, and H 2 /CO ratio than NAC-I catalyst. Marinho et al (2020) found the positive effect of the sol-gel method on the stabilization of Ni particle size in the reduction process at high temperature (800 • C) Ni@CeO 2 . Besides, the above catalysts prepared by the sol-gel method also generated more oxygen vacancies and stronger metal-support interaction with CeZrO 2 and Ni than the impregnated Ni/CeO 2 catalyst.…”
Section: Preparation Methodsmentioning
confidence: 90%